2008
DOI: 10.2460/ajvr.69.7.880
|View full text |Cite
|
Sign up to set email alerts
|

Composition and electrophoretic mobility of plasma lipoproteins of dromedary camels (Camelus dromedarius)

Abstract: The lipoprotein profile in 1-humped camels differed substantially from that of other ruminants. Results may be useful in the evaluation of metabolic disorders in camels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Phospholipids are a main component of the cell membrane, notably of the camel RBCs and contribute to their properties (Warda and Zeisig, 2000). In camel, PL was the major constituent of vLDL, LDL, and HDL which are important plasma lipoprotein carriers for cholesterol and triglycerides (Asadi et al, 2008). Gupta et al (2012) confirmed that the type of diet brought to camels influences cholesterol levels.…”
Section: Discussionmentioning
confidence: 80%
“…Phospholipids are a main component of the cell membrane, notably of the camel RBCs and contribute to their properties (Warda and Zeisig, 2000). In camel, PL was the major constituent of vLDL, LDL, and HDL which are important plasma lipoprotein carriers for cholesterol and triglycerides (Asadi et al, 2008). Gupta et al (2012) confirmed that the type of diet brought to camels influences cholesterol levels.…”
Section: Discussionmentioning
confidence: 80%
“…Another known drawback of the immunologic methods is that they fail to detect circulating triglyceride is found in VLDL and a further 15.5% in LDL. 50 Cholesterol is distributed mainly between LDL (58.5%) and HDL (24.7%). The ratio of cholesterol to triglyceride in VLDL is 0.12, in LDL is 1.92, and in HDL is 0.80.…”
Section: Energy Substratesmentioning
confidence: 99%